2022
DOI: 10.1590/s2175-97902022e20607
|View full text |Cite
|
Sign up to set email alerts
|

Impact of supplemental vitamins and natural honey for treatment of COVID-19: A review

Abstract: The main aim of the paper is to assess whether vitamin C, vitamin D, and natural honey can be administered in the course of the COVID-19 pandemic for promising in line methods with recent evidence. Both systematic literature and clinical trial identification were conducted by searching various databases. A total 58 articles and 29 clinical trials were selected wherein 11 for vitamin C, 16 for vitamin D, and 2 for natural honey were identified for analysis. The high doses of vitamin C (i.e. '200 mg/kg body weig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 56 publications
(49 reference statements)
0
2
0
Order By: Relevance
“…Similarly, another review suggested honey as an adjuvant in the treatment of COVID-19 infection, stating its antiviral properties related to its antioxidant and anti-inflammatory attributes and urging more clinical trials in the future [ 47 ]. Supplemental vitamins C, vitamin D, and natural honey, according to a review, seem promising to alleviate symptoms and disease progression alongside conventional treatment of COVID-19, however, more extensive clinical validation is essential [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, another review suggested honey as an adjuvant in the treatment of COVID-19 infection, stating its antiviral properties related to its antioxidant and anti-inflammatory attributes and urging more clinical trials in the future [ 47 ]. Supplemental vitamins C, vitamin D, and natural honey, according to a review, seem promising to alleviate symptoms and disease progression alongside conventional treatment of COVID-19, however, more extensive clinical validation is essential [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Historically, honey has been used as an alternative medicine to treat wounds, tissue regeneration, alleviating gastrointestinal disorders, gingivitis and various other pathologies (Ilia et al ., 2021; Akaba et al ., 2023). Honey has been reported to possess antimicrobial (Carnwath et al ., 2014), antiviral (Rabby et al ., 2022), anti‐inflammatory (Yu et al ., 2023), antioxidant (Mohamed et al ., 2011; Zubi et al ., 2023), antimutagenic (Saxena et al ., 2012) and antitumor effects (Fukuda et al ., 2011). Honey also possesses protective effects on the cardiovascular, nervous, respiratory and gastrointestinal systems (Alvarez‐Suarez et al ., 2013; Cianciosi et al ., 2018) and is licensed as a medical product for professional wound care in Europe, Australia, New Zealand, Hong Kong and the USA (Irish et al ., 2011).…”
Section: Introductionmentioning
confidence: 99%